Mainstreaming SMEs: Promoting inclusive growth in APEC - Erlinda M. Medalla; Melalyn C. Mantaring (Philippine Institute for Development Studies (PIDS), 2017)
Small and medium enterprise (SME) development as a major domestic policy objective that is consistent and reinforced within APEC would not only engender inclusive growth but also enable SMEs to become drivers of growth for the domestic, as well as the regional economy. This paper provides a background on the local SME development policy environment and the existing APEC SME activities in the region. It also offers recommendations on how the APEC can further mainstream SMEs in the regional and global market.
Keywords: 330; APEC; inclusive growth; SMEs; small and medium enterprises